Correlation between burnout and professional value in Chinese oncology nurses: A questionnaire survey - Fang Cheng; Ai-feng Meng; Tao Jin (Elsevier, 2015)
Objective: To investigate the relationship between job burnout and professional value in oncology nurses. Methods: The Maslach Burnout Inventory (MBI) and the Nurse Professional Values Scale (NPVS) were administered to nurses (n = 328) at the Cancer Hospital of Jiangsu Province, China, and the correlation between job burnout and professional value was calculated. Results: The scores (mean ± standard deviation) of emotional exhaustion (25.32 ± 12.37), depersonalization (6.93 ± 5.28), and personal accomplishment (30.25 ± 8.96) were measured, indicating a high level of burnout among oncology nurses. Also measured, were the four domains of professional value: caring (36.39 ± 5.73), actionist (21.17 ± 4.85), responsibility freedom and safety (17.95 ± 2.96), and reliability (11.44 ± 1.98). Job burnout and caring were positively correlated (p < 0.01), suggesting that caring was the number one concern of oncology nurses. Clinical implication: The prevalence of job burnout in oncology nurses is high, and this could be improved by increasing perception of professional value. It is urgent for managers to strengthen professional value education and to take strategies that reduce job burnout, which is important for the overall quality and safety of nursing.